MENINGKATKAN KONSENTRASI BELAJAR ANAK DENGAN METODE BERCERITA DI TK AL – IMAN - Masytah, Qonita Tillah; Muzaqi, Sugito (Universitas Narotama, 2023)
This study aims to improve early childhood learning concentration by applying the storytelling method. The method used in this research is classroom action research with observation and documentation data collection techniques. Observations were made to observe the level of children's learning concentration with the application of storytelling methods carried out both using picture storybook media and using hand puppets. The results of the observation research carried out were in the pre-cycle activities the percentage value obtained was 50% (sufficient category), in the application of the storytelling method in cycle I using picture book media the percentage observation results increased by 72% (good category), the research was continued in cycle II due to the percentage observation results had not reached the target of 75%, in cycle II the application of the storytelling method using hand puppet media was carried out, in this cycle II action the percentage figure experienced a significant increase of 95% (very good category). From the results of cycle II this research was declared successful because the percentage figure had exceeded 75%. Keywords: Concentration Difficulty, Storytelling Method, Media.